Pelaksanaan Evaluasi Pembelajaran PAI Pada Siswa Inklusi - Taufiki Rahman; Salmiwati Salmiwati; Alimir Alimir; Fauzan Fauzan (Politeknik Kampar, 2024)
This research is motivated by problems related to the implementation of learning evaluations by PAI teachers on inclusive students, that in carrying out learning in the classroom teachers still often equate evaluations between inclusive students and ordinary students. Ideally, in carrying out evaluations on inclusive students, teachers must design learning that will be able to accommodate inclusive students. The aim of this research is to find out how PAI learning evaluation is carried out for inclusive students at SDN 04 Birugo. This type of research is qualitative research with descriptive methods, data collection techniques using observation, interviews and documentation. The results of this research are that PAI teachers have carried out learning evaluations for inclusive students in PAI subjects by modifying learning with indicators a. Extended assessment time, b. The questions used are different from children in general c. Evaluation is carried out in certain places, individually. d. Graduation standards and minimum graduation competencies (KKM) remain the same e. The reporting system uses the same system found in the Dapodik application. The automatic grade promotion system and the diploma system are the same.